2023
DOI: 10.1097/ms9.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and incidence of colorectal polyps: a case-controlled study

Abstract: Background: Previous essays have presented possible concordance between obesity and colorectal polyp development. However, neither for the hypothesis nor for the details general consensus exists. This study aimed to evaluate the association between higher BMI rather than the normal and colorectal polyp presentation and characteristics if any. Methods: Eligible patients based on study criteria who were candidates for total colonoscopy examination enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…32 36 The chance for colorectal polyps was higher in obese people, so the chance of developing polyps increased with increasing BMI. Previous studies have shown an association between BMI and colorectal polyps, 4 19 37 but not exclusively. 4 38…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…32 36 The chance for colorectal polyps was higher in obese people, so the chance of developing polyps increased with increasing BMI. Previous studies have shown an association between BMI and colorectal polyps, 4 19 37 but not exclusively. 4 38…”
Section: Discussionmentioning
confidence: 90%
“…32,36 The chance for colorectal polyps was higher in obese people, so the chance of developing polyps increased with increasing BMI. Previous studies have shown an association between BMI and colorectal polyps, 4,19,37 but not exclusively. 4,38 In this study, polyp prevalence was not statistically significantly associated with WHR, but the chance of polyp development increased with high-risk WHR.…”
Section: Number Of Diverticulamentioning
confidence: 90%
See 1 more Smart Citation